Design of a new energy dissipating device and verification for use in rockfall protection barriers. (15th November 2019) - Castanon-Jano, Laura; Blanco-Fernandez, Elena; Castro-Fresno, Daniel
Highlights: A new modular brake mainly based on the deformation of its components is designed. The drawback of the irregular behaviour curves on friction-type brakes is removed. An optimal geometry is found by means of experimental and numerical methods. The inclusion of brakes on a barrier FEM model increased its energy capacity a 61% Abstract: Flexible barriers are structures used to protect specific areas from falling rocks. In most cases, barriers have energy dissipating devices (or brakes), that help to increase their energy-dissipation capacity by deformation, friction or the two mechanisms together. One drawback that has been detected in existing brakes is that they usually display irregular behaviour so that their real performance can present unexpected results in terms of activation force or total energy absorbed. This paper presents the complete design procedure of a new brake, which is proposed as a potential alternative to solve these uncertainties. The main energy dissipation mechanism is by plastic deformation of its components. The design procedure combines experimental tests and numerical modelling to take advantage of the benefits of both techniques. The final geometry is selected considering its efficiency, which involves not only total absorbed energy, but also energy absorbed per unit of mass.